The big freeze : a reporter's personal journey into the world of egg freezing and the quest to control our fertility - Lampert, Natalie (Ballantine Books, 2024)
"A fascinating investigation into the lucrative, minimally regulated, fast-growing industry of egg freezing, from a young reporter on a personal journey into the world of cutting-edge reproductive medicine"--